2008
DOI: 10.1016/j.exer.2008.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct processes are evident in rat cone flicker ERG responses at low and high temporal frequencies

Abstract: The electroretinogram (ERG) provides a noninvasive, objective measure of retinal function, and is one of the most widely used diagnostic tools in the study of visual disorders. Although rodents are often used in the study of retinal disease, the properties of the flicker ERG of the rodent retina have not been fully characterized. Here, we show that the fundamental response of the rat ERG to sinewave flicker exhibited a low-pass pattern in the frequency range from 2 to 30 Hz, whereas the second harmonic (F2) sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 20 publications
6
30
0
Order By: Relevance
“…For the response elicited by sine-wave modulated light stimuli, the amplitudes of the fundamental responses at each respective stimulus frequency are plotted. In agreement with our previous report (Qian et al, 2008), the amplitude of the fundamental response to sine-wave flicker exhibited a monotonic low-pass pattern.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…For the response elicited by sine-wave modulated light stimuli, the amplitudes of the fundamental responses at each respective stimulus frequency are plotted. In agreement with our previous report (Qian et al, 2008), the amplitude of the fundamental response to sine-wave flicker exhibited a monotonic low-pass pattern.…”
Section: Discussionsupporting
confidence: 80%
“…In all flash luminosities tested, humps in high harmonic components were observed in pulse flicker ERG responses. It has been reported that, for sine-wave flicker ERG, responses elicited from rat eyes exhibit two distinct processes at low and high temporal frequencies (Qian et al, 2008). In particular, the contrast-response relation is linear when tested with a low-frequency (6 Hz) stimulus, but saturated in response to a high-frequency (20 Hz) stimulus.…”
Section: Effects Of Flash Intensity On Pulse Flicker Ergmentioning
confidence: 99%
See 3 more Smart Citations